The role of cardiovascular calcifications in COVID-19. (14th October 2021) - Toselli, M; Cereda, A C; Giannini, F G; Scoccia, A S; Gallone, G G; Palmisano, A P; Vignale, D V; Esposito, A E
Abstract: Background: Coronary, thoracic aorta and aortic valve calcium can be measured from a non-gated chest computer tomography (CT) and are validated predictors of cardiovascular events and all-cause mortality. However, their prognostic role in acute systemic inflammatory diseases, such as COVID-19, has not been investigated. Purpose: The principal aim was to evaluate the association of coronary artery calcium (CAC) and total thoracic calcium on in-hospital mortality in COVID-19 patients. Then, to evaluate the prognostic impact of clinical and subclinical coronary artery disease (CAD), as assessed by CAC. Methods: 1093 consecutive patients from 16 Italian hospitals with a positive swab for COVID-19 and an admission chest CT for pneumonia severity assessment were included in the SCORE COVID-19 registry (calcium score for COVID-19 Risk Evaluation). At CT, coronary, aortic valve and thoracic aorta calcium were qualitatively and quantitatively evaluated separately and combined together (total thoracic calcium) by a central Core-lab blinded to patients' outcomes. A specific sub analysis on CAC was performed stratifying the patients in three groups: (a) "clinical CAD" (prior revascularization history), (b) "subclinical CAD" (CAC >0), (c) "No CAD" (CAC=0). In-hospital mortality was the primary endpoint, while a composite of myocardial infarction and cerebrovascular accident (MI/CVA) was the secondary one. Results: Non-survivors compared to survivors had higher coronary artery [(487.7±565.3 vs 207.7±406.8, p<0.001)], aortic valve [(322.4±390.9 vs 98.2±250.7 mm 2, p<0.001)] and thoracic aorta [(3786.7±4225.5 vs 1487.6±2973.1 mm 2, p<0.001)] calcium values. Coronary artery calcium (HR 1.308; 95% CI, 1.046 - 1.637, p=0.019) and total thoracic calcium (HR 1.975; 95% CI, 1.200 - 3.251, p=0.007) resulted to be independent predictors of in-hospital mortality. In the sub - analysis increasing rates of in-hospital mortality (11.3% vs. 27.3% vs. 39.8%, p<0.001) and MI/CVA events (2.3% vs. 3.8% vs. 11.9%, p<0.001) were observed from the No CAD to the clinical CAD groups. Among patients with subclinical CAD, increasing CAC burden was associated with higher rates of in-hospital mortality (20.5% vs. 27.9% vs. 38.7% for patients with CAC score thresholds ≤100, 101–400 and >400, respectively, p<0.001) Conclusion: Coronary, aortic valve and thoracic aortic calcium assessment on admission non-gated CT permits to stratify the COVID-19 patients in-hospital mortality risk. Cardiovascular calcifications may represent a bystander of an impaired vascular reserve, both microvascular and endothelial, but also a sign of vascular senescence. Therefore, it can be considered an index of biological frailty, likely more accurate than age and other risk factors. Funding Acknowledgement: Type of funding sources: None.